Characterization of FAE1 in the zero erucic acid germplasm of Brassica rapa L - Yan, Guixin (Breeding science, 2015)
The modification of erucic acid content in seeds is one of the major goals for quality breeding in oil-yielding Brassica species. However, few low erucic acid (LEA) resources are available, and novel LEA genetic resources are being sought. Fatty acid elongase 1 (FAE1) is the key gene that controls erucic acid synthesis. However, the mechanism for erucic acid synthesis in B. rapa lacks systematic study. Here, we isolated zero erucic acid lines from 1981 Chinese landraces of B. rapa and found that the formation of LEA is not attributable to variations in FAE1 coding sequences, as reported for B. napus, but may be attributable to the decrease in FAE1 expression. Moreover, the FAE1 promoter sequences of LEA and high erucic acid materials shared 95% similarity. Twenty-eight bases deletions (containing a 24-base AT-rich region) were identified approximately 1300 bp upstream from the FAE1 start codon in the LEA accessions. The genotype with the deletions co-segregated with the LEA trait in the segregating population. This study isolated an LEA B. rapa resource that can be exploited in Brassica cultivation. The promoter variations might modify the expression level of FAE1, and the results shed light on novel regulation mechanisms for erucic acid synthesis